Hautalterung und evidenzbasierte topische Anti-Aging-Strategien = Skin aging and evidence-based topical strategies - Bayerl, Christiane (Der Hautarzt, 2016)
Anti-aging in dermatology primarily focuses on the prevention of skin aging with UV protection (clothing and sunsceens), free radical scavengers (synthetic or botanic), and cell-protecting agents such as vitamin B3. For the correction of signs of early skin aging, retinoic acid derivatives in dermatological prescriptions are the best studied substances. Topical hormonal prescriptions are also an option if UV damage has not been the leading culprit for aging. Chemical peeling leads to a marked increase in collagen formation, the deaper the better. Ingredients in cream preparations can reduce superficial skin folds (polyphenols, amino acid peptides). Modulators of regular pigmentation are important for anti-aging preparations. Growth factors (plant extracts, recombinant growth factors) are not thoroughly studied regarding the cost-benefit and risk ratio. Complex precedures such as photodynamic therapy have an impact on the appearance of aged skin.